Распределение биомассы фитопланктона в Красном море и Аденском заливе - (:unkn) unknown (Киев : Наук. думка, 1974)
Приводятся материалы по распределению биомассы фитопланктона, собранные зимой 1961/62 г., летом и осенью 1963 г. Выявлена зависимость в распределении биомассы от условий абиотической среды, в частности гидрологических и гидрохимических характеристик. Установлена связь между распределением биомассы фитопланктона и характером поступления вод Аденского залива. Отмечена общая тенденция в распределении фитопланктона в море: увеличение показателей количественного развития с севера на юг. Выявлены сезонные колебания величин биомассы фитопланктона. Максимум ее (215 мг/м³) наблюдался летом. Осенью и зимой величины биомассы были значительно ниже — соответственно 60,2 и 24,4 мг/м³. Колебания величин биомассы фитопланктона и изменение местоположения наиболее продуктивных районов в Красном море и Аденском заливе в значительной степени определяются изменениями циркуляции течений, обусловленных сезонными изменениями муссонных ветров.
Distribution of phytoplankton biomass in the Red Sea and Aden Bау
Indices of phytoplankton quantitative development in the Red Sea are determined to a considerable extent by delivery of the Aden Bay waters rich in biogenic elements and their distribution over the aquatorium. A typical peculiarity was revealed in the Red Sea phytoplankton distribution during all the periods of observations: an increase in the phytoplankton quantitative characteristics from the North to the South. It was especially distinct in distribution of Diatomeae. A high content of biogenic elements in the waters of Aden Bay and the southern part of the Red Sea observed almost the whole year round creates here favourable conditions for a relatively intensive development of planktonic algae and on their base — the subsequent links of the food chain. Maximum values of the phytoplankton biomass (above 200 mg/m³) were observed in the Red Sea in summer with most intensive delivery of the Aden waters into the photosynthesis zone and a higher phosphate content in them. In winter and autumn the biomass values are considerably lower — 24.4 and 60.2 mg/m³, respectively.